Audit of red blood cell transfusion in patients with acute leukemia at a tertiary care university hospital. Issue 4 (14th February 2020) - Jaime‐Pérez, José Carlos; García‐Salas, Gerardo; Áncer‐Rodríguez, Jesús; Gómez‐Almaguer, David
Abstract : BACKGROUND: Red blood cell (RBC) transfusion support is essential in patients with acute leukemia (AL). A restrictive RBC transfusion approach is assumed to be safe for most individuals with AL. The aim of this audit was to assess RBC transfusion appropriateness in AL patients at an academic center. STUDY DESIGN AND METHODS: RBC transfusions in acute lymphoblastic leukemia and acute myeloid leukemia patients of all ages between January 1, 2013, and March 31, 2019, were analyzed for adherence to evidence‐based criteria. Transfusion appropriateness was compared among ordering specialties, patient locations, and hematologic diagnoses. Pretransfusion hemoglobin was compared between categories. Overtransfusion rates were also analyzed. Descriptive statistics and categorical and numerical tests were employed to determine statistical significance. RESULTS: A total of 510 RBC transfusions were received by 133 AL patients in the departments of internal medicine, hematology, and pediatrics. Overall, 84.5% were appropriate according to established criteria. Internal medicine was the ordering department with the highest rate of appropriateness (88.1%). The outpatient clinic was the location with the highest adherence (85.9%), whereas the intensive care unit had the lowest (70%; p = 0.03). The reasons for most appropriate and inappropriate transfusions were asymptomatic anemia with a hemoglobin below (60.6%) or above (69.6%) 7 g/dL in patients without cardiac disease, respectively. Overtransfusion was present in 22% of episodes. CONCLUSION: RBC transfusion in AL patients reflected good adherence to guidelines. However, continuing education in transfusion medicine and prospective chart auditing are needed to improve adherence to established guidelines.